Implementasi Strategi Pembelajaran Kurikulum 2013 Saintifik pada Mata Pelajaran Agama di Kelas 5 SD Kartika I-2 Medan - Arlina Arlina; Rini Amelia Siagian; M. Akbar Thoha; Arjuna Barkah Firdaus (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This research aims to describe the implementation of the 2013/Scientific curriculum learning strategy and describe the advantages and disadvantages of applying scientific implementation to learning. The implementation of learning through the teaching and learning process is basically the core of education as a whole. Teachers as educators who participate directly in the learning process are obliged to ensure that students are active in the learning process by using appropriate learning models. The type of research used in this study is descriptive qualitative to obtain complete and in-depth descriptions in the form of written and spoken words of people and observable behavior. Information is analyzed by reducing data, describing data and drawing conclusions. This research is to identify how strategies are implemented in religious subjects at SD Kartika I- 2. This research examines teachers' teaching strategies in religious subjects using the 2013/Scientific curriculum learning strategies.